Evaluation of Indian Durum Wheat Genotypes for Yield and Quality Traits Using Additive Main-Effects and Multiplicative Interaction (AMMI) Biplot Analysis under Terminal Heat Stress Conditions - Gautam, Amit; Venkata Sai Prasad, Sukuru; Jajoo, Anjana; Bassi, Filippo (Hapres, 2023)
The abrupt increase of temperatures during and after the flowering period of wheat is defined as terminal heat stress, and it causes severe reductions in productivity. One hundred two durum wheat lines were evaluated against this stress for three consecutive cropping seasons (2014–2017) in Indore, Madya Pradesh (India). The main objectives were to assess their grain yield potential, stability, and rheological quality characteristics under these conditions, and identify other contributing traits to adaptation. Combined ANOVA across environments showed significant differences (P < 0.01) for all factors, and high broad sense heritability was recorded for hectoliter weight, 1000-grains weight, grain yield, number of grains per spike, spike length, days to maturity, total carotene and sedimentation values. Grain yield showed significant (P < 0.01) positive associated with biomass, harvest index, hectoliter weight and significant negative associations with day to heading and maturity. Genotypes showed explicit variation to environmental condition as supported by significant (P < 0.01) for genotype × environment interaction (GEI). The traits like early heading, maturing, high biomass and hectoliter weight were the most critical traits for adaptation under terminal heat stress. To determine effects of GEI data were subjected to GGE biplot analysis, which identified as the most stable and performing across seasons G-30 (GW 1240) for hectoliter weight and G-98 (Vijay) for grain yield. These entries can now be combined via breeding to develop superior heat stress tolerant varieties.